2012
DOI: 10.1097/pas.0b013e3182395c7b
|View full text |Cite
|
Sign up to set email alerts
|

HPV Analysis in Distinguishing Second Primary Tumors From Lung Metastases in Patients With Head and Neck Squamous Cell Carcinoma

Abstract: For patients with head and neck squamous cell carcinoma (HNSqCC), the development of squamous cell carcinoma (SqCC) in the lung may signal a new primary or the onset of metastatic dissemination. Although the distinction influences prognosis and therapy, it may not be straightforward on histological or clinical grounds. Human papillomavirus (HPV) is an etiologic agent for SqCCs arising from the oropharynx, but not for SqCCs arising from other head and neck sites. For patients with HNSqCC who develop a lung SqCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 33 publications
0
61
0
2
Order By: Relevance
“…Sunnybrook Health Sciences Centre, 2075 range of HPV infection detected in lung ADC occurring in Asian populations varies from 0 to around 40% [7][8][9]. In contrast, several studies based on North American and European populations did not find an association between HPV infection and NSCLC [10][11][12][13]. A recent comprehensive meta-analysis [6] and an international pooled analysis [14] found that the variation in HPV detection rate may be a function of the geographical origin and histologic subtypes, rather than detection methods.…”
Section: Introductionmentioning
confidence: 95%
“…Sunnybrook Health Sciences Centre, 2075 range of HPV infection detected in lung ADC occurring in Asian populations varies from 0 to around 40% [7][8][9]. In contrast, several studies based on North American and European populations did not find an association between HPV infection and NSCLC [10][11][12][13]. A recent comprehensive meta-analysis [6] and an international pooled analysis [14] found that the variation in HPV detection rate may be a function of the geographical origin and histologic subtypes, rather than detection methods.…”
Section: Introductionmentioning
confidence: 95%
“…Some previous evidences have approved the common risk factors and molecular abnormalities in cell-cycle regulation and signal transduction predominate among these three cancers. For example, for those patients with head and neck squamous cell carcinoma, the development of squamous cell carcinoma in the lung may signal a new primary or the onset of metastatic dissemination [16]. Previous study suggested that the INK4a/p16 germline mutation associated with familial atypical multiple mole melanoma syndrome can also be associated with familial head and neck squamous cell carcinoma syndrome [17].…”
Section: Exploration the Cancers Association Based On The Associationmentioning
confidence: 99%
“…However, current data suggest that most of these HPV þ lung SCCs may represent metastasis from previous head and neck HPV þ SCC and uterine or cervical HPV þ lesions and SCC. 17,18 Basaloid carcinoma of the lung is an uncommon poorly differentiated NSCLC, probably akin to SCC. Histologically, the tumor is composed of relatively small cells with high numbers of mitotic figures showing a lobular pattern with peripheral palisading and comedo-type necrosis.…”
Section: Primary Lung Adc and Sccmentioning
confidence: 99%